PENGARUH GAYA BELAJAR TERHADAP HASIL BELAJAR SISWA SETINGKAT SEKOLAH MENENGAH PERTAMA - Zakiya Qothrun Nada; Didit Darmawan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Education is a means to build a better future. Learning outcomes show students' achievements in understanding the learning process. Learning style is known to be a factor that determines learning outcomes. This literature study examines the influence of learning styles on the learning outcomes of junior high school students in various junior high schools in Indonesia. This research uses a qualitative method based on a literature study approach to explore the influence of learning styles on student learning outcomes. The analysis uses descriptive analysis using the literature results that have been found. The purpose of implementing the literature study method in this research is as an initial step in planning research to utilize literature to obtain data in the field without the need to go directly. The results of this research reveal that learning styles greatly influence student learning outcomes.